'60 - '80; attitudes, concepts, images; stedelijk museum Amsterdam, 9.4. - 11.7.1982. - Stedelijk Museum Amsterdam (Amsterdam : Van Gennep, 1982)
Abramovic, Marina & Ulay ; Acconci, Vito ; Ader, Bas Jan ; Anderson, Laurie ; Andre, Carl ; Arman ; Armando ; Bacon, Francis ; Baselitz, Georg ; Ben ; Beuys, Joseph ; Boltanski, Christian ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Cage, John ; Carter, Elliott ; Chia, Sandro ; Christo ; Constant ; Cucchi, Enzo ; Cunningham, Merce ; d'Armagnac, Ben ; Daniels, René ; Darboven, Hanne ; Dekkers, Ad ; Dibbets, Jan ; Dine, Jim ; Dubuffet, Jean ; van Elk, Ger ; Eno, Brian ; Fabro, Luciano ; Fontana, Lucio ; Forti, Simone ; Gilbert & George ; Graham, Dan ; de Groot, Pauline ; Gudmundsson, Sigurdur ; Haacke, Hans ; Hamilton, Richard ; Heyboer, Anton ; Hockney, David ; van Hoek, Hans ; Hoover, Nan ; Jenney, Neil ; Johns, Jasper ; Jonas, Joan ; Kawara, On ; Kelly, Ellsworth ; Kiefer, Anselm ; Kienholz, Edward ; Klein, Yves ; de Kooning, Willem ; Kosuth, Joseph ; Kounellis, Jannis ; LeWitt, Sol ; Lichtenstein, Roy ; Long, Richard ; Lucassen ; Lucebert ; Manzoni, Piero ; Marden, Brice ; Martin, Agnes ; Matta-Clark, Gordon ; Merz, Mario ; Mol, Pieter Laurens ; Monk, Meredith ; Morris, Robert ; Musica Elettronica Viva MEV ; Nauman, Bruce ; Newman, Barnett ; Oldenburg, Claes ; Oppenheim, Dennis ; Paik, Nam June ; Palestine, Charlemagne ; Paolini, Giulio ; Penone, Giuseppe ; Raetz, Markus ; Rainer, Yvonne ; Rauschenberg, Robert ; Raveel, Roger ; Raysse, Martial ; Richter, Gerhard ; Rosenbach, Ulrike ; Roth, Dieter ; Rückriem, Ulrich ; Ruscha, Edward ; Ryman, Robert ; Schippers, Wim T. ; Schnabel, Julian ; Schoonhoven, Jan ; Serra, Richard ; Sharits, Paul ; Smith, Barbara T. ; Snow, Michael ; Soto, Jesus Rafael ; Spoerri, Daniel ; Stella, Frank ; Tinguely, Jean ; Tudor, David ; Tuttle, Richard ; Uecker, Günther ; Uitti, Frances-Marie ; Verkerk, Emo ; etc.
boek